Challenges and opportunities for printed electrical gas sensors - Barandun,G; Gonzalez,Macia ML; Lee,HS; Dincer,C; Guder,F (ACS Sensors, 2022)
Printed electrical gas sensors are a low-cost, lightweight, low-power and potentially disposable alternative to gas sensors manufactured using conventional methods such as photolithography, etching and chemical vapor deposition. The growing interest in Internet-of-Things, smart homes, wearable devices and point-of-need sensors has been the main driver fueling the development of new classes of printed electrical gas sensors. In this Perspective, we provide an insight into the current research related to printed electrical gas sensors including materials, methods of fabrication, and applications in monitoring food quality, air quality, diagnosis of diseases and detection of hazardous gases. We further describe the challenges and future opportunities for this emerging technology.